2005
DOI: 10.1039/b418188c
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state dynamics of the fluorescent probe Lucifer Yellow in liquid solutions and in heterogeneous media

Abstract: The photophysics of the dye Lucifer Yellow ethylenediamine (LYen) has been investigated in various polar solvents. The main deactivation pathways of its first singlet excited state are the fluorescence and the intersystem crossing. In water, non-radiative decay by intermolecular proton transfer becomes a significant deactivation channel. The early fluorescence dynamics, which was investigated in liquids and in reverse micelles, was found to depend substantially on the environment. An important static quenching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 67 publications
8
87
0
Order By: Relevance
“…17,18 To draw the decay-associated amplitude spectra, the sum of the positive amplitudes was set equal to 1 at 495 nm (maximum intensity in the spectrum). Time-resolved emission spectra were reconstructed from the analytical expressions obtained for the decays from the fitting procedure.…”
Section: Methodsmentioning
confidence: 99%
“…17,18 To draw the decay-associated amplitude spectra, the sum of the positive amplitudes was set equal to 1 at 495 nm (maximum intensity in the spectrum). Time-resolved emission spectra were reconstructed from the analytical expressions obtained for the decays from the fitting procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, a blue shift is observed when the fluorophore LY was incorporated into p(NIPAM). This is due to the change in the environment around the LY such as the electronic cloud in the polymer particle p(NIPAM) as well as the polarity of the solvent [18]. The shift of the emission band also provides evidence (together with the DLS and IR) of the incorporation of LY in the new nanoparticle.…”
Section: Fluorescence Spectroscopymentioning
confidence: 86%
“…However, the fluorescence intensity of LY is significantly higher than that of p(NIPAM-co-5% LY) which suggests that either not all the LY added during the synthesis reaction is incorporated in the new particle, or the quantum yield of LY was quenched by the p(NIPAM) particles, or other environmental conditions such as solvent polarity [18]. The second suggestion is supported by Furstenberg et al [18] who studied the excited state dynamics of lucifer yellow and concluded that LY is an environment sensitive probe whose fluorescence dynamics change in the presence of proteins and by changing the solvent. They also concluded that the fluorescence of LY is quenched by amino acids.…”
Section: Effect Of Addition Of Lucifer Yellowmentioning
confidence: 86%
See 2 more Smart Citations